2017
DOI: 10.1098/rsos.170681
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive bias modification for facial interpretation: a randomized controlled trial of transfer to self-report and cognitive measures in a healthy sample

Abstract: Cognitive bias modification is a potential low-intensity intervention for mood disorders, but previous studies have shown mixed success. This study explored whether facial interpretation bias modification (FIBM), a similar paradigm designed to shift emotional interpretation (and/or perception) of faces would transfer to: (i) self-reported symptoms and (ii) a battery of cognitive tasks. In a preregistered, double-blind randomized controlled trial, healthy participants received eight online sessions of FIBM (N =… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Our mood state outcomes do not investigate this possibility. However, while a recent study of our CBM technique (Peters et al, 2017) with healthy participants showed little evidence of transfer of bias modification to a variety of cognitive tasks thought to be impacted by low mood, there was weak evidence of transfer to a measure of the impact of stressful events in daily life, particularly in those participants with higher baseline anxiety. This is consistent with Grafton et al .…”
Section: Discussionmentioning
confidence: 73%
“…Our mood state outcomes do not investigate this possibility. However, while a recent study of our CBM technique (Peters et al, 2017) with healthy participants showed little evidence of transfer of bias modification to a variety of cognitive tasks thought to be impacted by low mood, there was weak evidence of transfer to a measure of the impact of stressful events in daily life, particularly in those participants with higher baseline anxiety. This is consistent with Grafton et al .…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, we set out to gather a large dataset of existing trait anxiety scores from labs across multiple institutions who routinely collect trait anxiety measures in their behavioural and MRI studies 1,25,[41][42][43][44][45][46][47][48][49][50][51][52][53][54] . In order to control for possible confounds and examine interaction effects, we additionally collected the following variables: gender, age, whether and how participants were screened for affective/psychiatric disorders, and whether the study involved the presence of a stressor and/or pharmacological manipulation (see Methods for details).…”
Section: Introductionmentioning
confidence: 99%
“…In study 1, we examined the effectiveness of EBT in a sample of healthy volunteers to test the feasibility of conducting the EBT trial remotely and to explore Peters et al's (2017) finding that EBT may lead to a reduction in daily stress in healthy participants. Mental health and functional outcomes were assessed at baseline, immediately post-training, and at a 2-week follow-up.…”
mentioning
confidence: 99%
“…We hypothesised that four sessions of EBT would induce a positivity bias in the recognition of emotional facial expressions, as shown in previous laboratory-based research (Penton-Voak et al, 2012). We also hypothesised that this change in bias would transfer to decreased daily stress and greater motivation to seek reward (Peters et al, 2017). We also explored if EBT led to self-reported improvements in quality of life.…”
mentioning
confidence: 99%